(untitled) - Bermingham , Susan (Oxford, 2000)
The AS part of the syllabus encourages students to: acquire and apply knowledge and understanding of physical and human processes, their interactions over space and time, and relate this to particular events acquire and apply a range of skills develop an understanding of interrelationships between people and environments, and of the opportunities, challenges, and constraints that people face in their environments appreciate the dynamic nature of Geography understand how decisions are made clarify and develop values and attitudes
Keywords: Environmental science,Global environmental change